A unique case of isolated sebaceous adenoma of the bulbar conjunctiva - Ilhan,Hatice Deniz (2016)
ABSTRACT Our patient was a 34 year-old male who presented with a painless conjunctival mass that had developed 3 months before his first visit. On performing slit-lamp biomicroscopy, a lobulated pink-yellowish solid mobile mass was observed on the nasal bulbar conjunctival surface of his left eye. The tumor was excised, and histopathologic examination of the tumor revealed a sebaceous adenoma. Systemic examination was normal. No recurrence was observed during the 24-month follow-up period. Sebaceous adenoma of the bulbar conjunctiva is an extremely rare benign tumor, which may be observed to be isolated in the absence of malignancy.